Nomenclature savante et classement profane - Laurence Proteau (Les éditions de la Maison des sciences de l'Homme, 2005)
In the French public secondary schools, administrators (most often secretaries) are asked to enter the parents' occupations, which are frequently loosely specified by the families, into an official nomenclature, the Classification of Occupations and Social Groups (PCS) issued by INSEE in 1982. To carry out this task, they only have a computer list of socio-economic categories, a simplified version of the PCS. They therefore need to reinterpret the nomenclature. Because of a lack of specific training, they draw on their personal information based on their knowledge of the local area and, more importantly, on their own representations of the social division of labour, professional hierarchies, "prestigious" and "unprestigious" jobs, male and female jobs, etc. Thus, the construction of statistics on the social origins of the pupils, far from being a mere technical operation, integrates the perceptions and classifications of the social world and the local knowledge of school administrators.